The Influence of Building Quality, Facilities and Location of Flats on the Level of Occupant Satisfaction in Islamic Boarding School Flats in the Jambi Region - Sujono; Firdaus (PT FORMOSA CENDEKIA GLOBAL, 2024)
The aim of this research is to determine the quality of buildings, facilities and location of flats on the level of satisfaction of flats residents in the area, namely the As'ad Islamic Boarding School and Sa'adatuddaren Flats. The sample in this study is the residents of the As'ad Islamic Boarding School and Sa'adatuddaren Islamic Boarding School Flats, the method used is a quantitative method with SEM-Smart-PLS analysis techniques, the data used is primary and secondary data. Hypothesis testing uses weight relationships. The results of the research are that Building Quality does not have a significant effect on Resident Satisfaction, Facilities do not have a significant effect on Resident Satisfaction, Location Bepengaru has a significant effect on Resident Satisfaction, and Building Quality, Facilities and Lacation do not have a significant effect on Resident Satisfaction